Autistic traits impact on olfactory processing in adolescent girls with Anorexia Nervosa restricting type. (April 2019) - Tonacci, Alessandro; Calderoni, Sara; Billeci, Lucia; Maestro, Sandra; Fantozzi, Pamela; Ciuccoli, Federica; Morales, Maria Aurora; Narzisi, Antonio; Muratori, Filippo
Highlights: Adolescents with AN-R do not show any olfactory impairment with respect to controls. Olfactory performances are correlated with autistic traits in anorectic girls. Olfactory function varies with age in controls, but not in AN-R girls. Abstract: The correct functioning of the chemosensory pathway is pivotal for the attitude towards feeding. In some neuropsychiatric disorders, abnormalities of the sensory processing dramatically affect feeding behavior; however, evidences for an olfactory involvement in Anorexia Nervosa (AN) are still controversial. We administered a complete olfactory testing battery, the Sniffin' Sticks Extended Test, to a cohort of 19 girls with Restrictive Anorexia Nervosa (AN-R) and 19 healthy controls. A battery of questionnaires aiming to evaluate eating attitude, psychopathologic disorders and autistic traits was also administered. No difference was found between the two groups in any of the olfactory tasks. Despite the lack of correlation between olfaction and disease severity, however, olfactory performances were related to autistic traits in anorectic girls ( r  = −0.489, p  = 0.039). Girls with AN-R do not appear to have an impaired olfactory function with respect to controls. However, a possible correlation between olfactory ability and autistic traits was discovered. In light of such findings, the role of possible relations between social functioning-related features and olfactory processing in AN-R is discussed.